Motivasi Keusahawanan Dalam Perniagaan Kecil Dan Sederhana. Kajian Perbandingan Antara Usahawan Bumiputera Dengan Usahawan Bukan Bumiputera Di Johor Bahru. - Abdullah, Nurfarahin Jasmine See (2004)

(untitled)
The reason for this study is to see the difference among Bumiputera Entrepreneur with Non-Bumiputera Entrepreneur at Johor Bahru. This study is to identify the difference on the level of motivation that is : level 1 for physiology needs, level 2 for security needs, level 3 for social needs, level 4 for appreciation needs and level 5 for self actualization among them. Beside that this study do look into the difference of motivation characteristics that are level of initiative in running the business, the return of investment and the experience of running the business towards the level of motivation dimension for Bumiputera Entrepreneur and how far the achievement they achieve. Respondents of this study were the Bumiputera Entrepreneur that is 125 Malays and for Non-Bumiputera Entrepreneur there is 100 Chinese and 25 Indian at location of Johor Bahru. There are difference in the dimension level 1 for physiology needs and level 5 for self-actualization. The differences among the entrepreneur by looking into the questionnaires in the dimension and it’s found that Bumiputera Entrepreneur answer the questionnaire in the dimension level 1 and 5 difference then the Non-Bumiputera Entrepreneur. Elsewhere the others levels of dimension that are level 2 for security needs, level 3 for social needs, level 4 for appreciation needs are no differences among the Bumiputera Entrepreneur and Non Bumiputera Entreprenenur at Johor Bahru.